EndoGene database: reported genetic variants for 5,926 Russian patients diagnosed with endocrine disorders - Buzdin, Anton A.; Zolotovskaia, Marianna A.; Roumiantsev, Sergey A.; Emelyanova, Aleksandra G.; Golounina, Olga O.; Pugacheva, Polina A.; Luppov, Daniil V.; Kuzminyh, Anastasia V.; Alexeeva, Arseniya O.; Emelianova, Anna A.; Novoselov, Alexey L.; Matrosova, Alina; et al. (Frontiers in Endocrinology, 2025)
IntroductionEndocrine system disorders are a serious public health burden and can be caused by deleterious genetic variants in single genes or by the combined effects of multiple variants along with environmental and lifestyle factors.MethodsThe EndoGene database presents the results of next-generation sequencing assays used to genetically profile 5,926 patients who were diagnosed with 450 endocrine and concomitant diseases and were examined and treated at the National Medical Research Center for Endocrinology between November 2017 and January 2024. Among them, 494, 1,785, 692, and 1,941 patients were profiled using four internally developed genetic panels including 220, 250, 376, and 382 genes, respectively, selected based on a literature analysis and clinical recommendations, and 1,245 patients were profiled by whole exome sequencing covering 31,969 genes.Results2,711 genetic variants were reported as clinically relevant by medical geneticists and are presented here along with genomic, technical, and clinical annotations.DiscussionThis publicly accessible database will be useful to those interested in genetics, epidemiology, population statistics, and a better understanding of the molecular basis of endocrine disorders.